THE INFLUENCE OF HUMAN RESOURCES DEVELOPMENT ON THE PERFORMANCE OF THE STATE CIVIL APPARATUS IN THE AGENCY OF PERSONNEL AND HUMAN RESOURCES DEVELOPMENT IN THE CITY OF MAKASSAR - Permatasari, Nilam; Hasbiah, Sitti; Kurniawan, Agung Widhi; Musa, Chalid Imran; Haeruddin, M. Ikhwan Maulana (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The effective development of human resources plays a crucial role in enhancing organizational performance. In today's competitive environment, organizations recognize the significance of investing in the development of their employees to achieve sustainable success. The Makassar City Regional Personnel and Human Resource Development Agency, like many other institutions, seeks to optimize the performance of its State Civil Apparatus (ASN) employees. However, limited research has specifically explored the relationship between human resource development and employee performance within this context. This study aims to investigate the influence of human resource development on the performance of ASN employees at the Makassar City Regional Personnel and Human Resource Development Agency. The study utilizes primary and secondary data from a sample of 69 individuals. A quantitative approach is employed, and the data is analyzed using simple linear regression analysis. Questionnaires were distributed to the ASN employees, and various analysis techniques were applied, including validity and reliability tests, classical assumption tests, heteroscedasticity tests, hypothesis testing (T test), and coefficient of determination. The findings reveal a significant positive influence of human resource development on employee performance. This implies that increased levels of HR development led to improved employee performance. Therefore, it can be concluded that human resource development significantly affects the performance of ASN employees at the Makassar City Regional Personnel and Human Resource Development Agency.